2019
DOI: 10.5944/openpraxis.11.2.916
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Intervention of OER Renewable Assignments in a College Course

Abstract: The purpose of this study was to explore students and instructor perceptions of the concept of renewable assignments in the open educational resources (OER) movement. Mixed methods were used, with a combination of a survey and semi-structured interview, administered at George Mason University in the United States. Eleven graduate students enrolled in the Instructional Design and Technology program in the course Advanced Instructional Design were invited to complete an online survey. A face-to-face interview wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…The affordances of open licensing were also described as crucial for open pedagogy across several studies. Indeed, the description of open pedagogy in several of the studies specifically mentioned open licensing (Al Abri & Dabbagh, 2019;Kruger & Hollister, 2020;Nascimbeni & Burgos, 2019;Sheu, 2020;Tillinghast et al, 2020). However, there were variations across definitions even with those focused on open licensing.…”
Section: Rq1: Open Pedagogy Definitions/explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The affordances of open licensing were also described as crucial for open pedagogy across several studies. Indeed, the description of open pedagogy in several of the studies specifically mentioned open licensing (Al Abri & Dabbagh, 2019;Kruger & Hollister, 2020;Nascimbeni & Burgos, 2019;Sheu, 2020;Tillinghast et al, 2020). However, there were variations across definitions even with those focused on open licensing.…”
Section: Rq1: Open Pedagogy Definitions/explanationsmentioning
confidence: 99%
“…However, there were variations across definitions even with those focused on open licensing. In some studies, the focus was on student-created OER in terms of open licensing (Al Abri & Dabbagh, 2019;Hare et al, 2020;Hollister, 2020;Tillinghast et al, 2020). In others, the focus was on the value of the student artefacts beyond the class (e.g., Baran & Al Zoubi, in press;Bloom, 2019).…”
Section: Rq1: Open Pedagogy Definitions/explanationsmentioning
confidence: 99%
“…NDAs are central to open pedagogy. As student work extends beyond the student-teacher relationship and potentially benefits others, NDAs are hypothesized to increase student engagement and motivation (Al Abri & Dabbagh, 2019;Allan et al, 2018;Farzan & Kraut, 2013;Hilton et al, 2019;Jhangiani, 2017;Seraphin et al, 2019;Sheu, 2020;Stommel, 2015;Wiley, 2013). Students acting as content creators has the added benefit of fostering learner agency and shifting the course structure to a more student-empowered, studentcentered experience (DeRosa & Robison, 2017).…”
Section: Non-disposable Assignmentsmentioning
confidence: 99%
“…NDAs are those that provide value to others, are available to wider audiences, and may be licensed openly (Wiley & Hilton, 2018). Using NDAs may allow learners to attribute greater value to their efforts (Al Abri & Dabbagh, 2019;Allan et al, 2018;Farzan & Kraut, 2013;Hilton et al, 2019;Jhangiani, 2017;Sheu, 2020). Evidence suggests that this approach has the potential to positively impact student skill, achievement, and engagement (Hilton et al, 2019;Marsh, 2018;Sheu, 2020;Wiley et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, 60% of the students intended for works to be shared online or for the work to live beyond the class. A recent article by Al Abri and Dabbagh (2019) briefly touched on the idea of licensing. Survey responses in their study indicated that while most of the students were open to sharing their work, a few were reticent based on their lack of knowledge regarding OER, particularly as it related to licensing that allowed others to change their work.…”
Section: Literature Reviewmentioning
confidence: 99%